2020
DOI: 10.1177/1932296820967335
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c Is Disproportionately Higher in Women and Older People With Type 1 Diabetes Compared With Flash Glucose Monitoring Metrics of Glycemic Control

Abstract: Aims: Discrepancy between HbA1c and glucose exposure may have significant clinical implications. We sought to assess predictors of disparity between HbA1c and flash monitoring metrics and how these relate to microvascular complications. Methods: We conducted a cross-sectional study of adults with type 1 diabetes ( n = 518). We assessed the relationship between clinic HbA1c and flash monitoring metrics, predictors of discrepancy between these measurements, and whether discrepancy was associated with microvascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This is the first study to examine the association of HGI with diabetic complications and CGM metrics in Japanese adults with type 1 diabetes. In this study, a high HGI was significantly associated with female sex, as reported previously in people with a high risk of diabetes 34,35 . The relationship between HGI and female sex was consistent across studies.…”
Section: Discussionsupporting
confidence: 90%
“…This is the first study to examine the association of HGI with diabetic complications and CGM metrics in Japanese adults with type 1 diabetes. In this study, a high HGI was significantly associated with female sex, as reported previously in people with a high risk of diabetes 34,35 . The relationship between HGI and female sex was consistent across studies.…”
Section: Discussionsupporting
confidence: 90%
“…The demography of the study is represented in Table 1 showing all the parameters measured in T2DM individuals with and without retinopathy according to gender. (15).…”
Section: Resultsmentioning
confidence: 99%